2012
DOI: 10.1007/s11882-012-0324-x
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Performance and Application of Basophil Activation Tests

Abstract: The basophil activation test (BAT) is a flow-cytometry-based functional assay that assesses the degree of cell activation after exposure to a stimuli. Though no standardized technique currently exists, recent advances have improved the performance of this assay, including identification of new basophil-specific markers and comparisons of the expression of CD63 to CD203c during activation. The basophil activation test has also been validated for many IgE-mediated disease conditions, which have been extensively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 70 publications
(71 reference statements)
1
89
0
5
Order By: Relevance
“…[37][38][39] Notwithstanding, basophil response to allergens used in immunotherapy does not seem to fulfil all the expectations raised from a commonly accepted model of the basophil behavior toward an IgE-mediated mechanism. 31,40 For example, recent evidence showed that treatment with omalizumab results in a markedly increased sensitivity of basophils to an IgE-mediated stimulation in terms of the number of IgE molecules required to produce a given response. 41 Treatment with omalizumab in patients suffering from cat or peanut allergy enhanced the intrinsic sensitivity of circulating basophils as evaluated by histamine and LTC 4 release.…”
Section: Role Of Basophils In Immune System Following Immunotherapy: mentioning
confidence: 99%
See 2 more Smart Citations
“…[37][38][39] Notwithstanding, basophil response to allergens used in immunotherapy does not seem to fulfil all the expectations raised from a commonly accepted model of the basophil behavior toward an IgE-mediated mechanism. 31,40 For example, recent evidence showed that treatment with omalizumab results in a markedly increased sensitivity of basophils to an IgE-mediated stimulation in terms of the number of IgE molecules required to produce a given response. 41 Treatment with omalizumab in patients suffering from cat or peanut allergy enhanced the intrinsic sensitivity of circulating basophils as evaluated by histamine and LTC 4 release.…”
Section: Role Of Basophils In Immune System Following Immunotherapy: mentioning
confidence: 99%
“…In this context, the analytical assessment of allergy desensitization subsequent to immunotherapy may promote BAT as an eligible tool to highlight allergy in individuals undergoing treatment. 40,164 Particularly for omalizumab physicians and researchers have suggested this anti-IgE moAb as a reliable and promising tool against allergy, though with some raised criticism. [165][166][167][168][169] Omalizumab is an IgG 1 recombinant humanised monoclonal antibody which specifically binds to the Cε3 domain of immunoglobulin E, targeting the site of high-affinity IgE receptor binding.…”
Section: Immunotherapy With Monoclonal Anti-iges and Batmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is very important to detect specific antigens (also called allergens) and/or the sensitivity of IgE to the antigens, which induce allergic reactions in each patient. Various diagnostic tests for type I allergy, such as the detection of serum IgE, histamine release from basophils, or skin reactions to allergens, are performed [10][11][12][13][14][15][16][17]. In order to detect antigen-specific IgE in serum, ImmunoCAP TM , Ala-STAT TM , and AD-VIA Centaur TM have been developed and utilized in clinical practices [10].…”
Section: Introductionmentioning
confidence: 99%
“…Basophils also express several molecules on their surface, such as CD203c and CD69, which are used as activation markers. Therefore, the basophil histamine release test (HRT) and basophil activation test (BAT) for the detection of upregulation of CD203c or CD69 by flow cytometry are sensitive, safe, and offer reliable information regarding antigen that causes type I hypersensitivity in vitro [12,13]. Griese et al reported that the histamine release test showed higher sensitivity and specificity than the skin test or serum analysis, such as ImmunoCAP TM , based on the comparison with bronchoprovocation of extrinsic asthmatic children [14].…”
Section: Introductionmentioning
confidence: 99%